Effect of Circumferential Angle of Strake on Asymmetric Flow Over Blunt-Nosed Body - Siyu ZONG; Yankui WANG; Zhongyang QI (气体物理)
At a high angle of attack, asymmetric flow will be generated on the blunt-nosed body, leading to unpredictable side force. The regulation of asymmetric flow can be achieved by applying strakes with a specific height to the nose of the blunt-nosed body. To investigate the effect of the circumferential position of the strake on the asymmetric flow of a blunt-nosed body, the flow structures were analyzed at an angle of attack of 50° and a Reynolds number of 1.68×105, where the strake was placed at different heights and circumferential angles. The research findings indicate that the response relationship of the side force varies with the alteration of the strake height as the strake rotates circumferentially around the nose. The flow generated by the strake has a direct impact on the dominant role of the strake in controlling the asymmetric flow through the evolution on the leeward side of the model. When the height of strake is small, the control effect on the asymmetric flow is consistent irrespective of whether the strake is situated on the windward or leeward side. When the height is large, the evolution pattern of the vortex generated by the strake varies depending on whether the strake is located on the windward or leeward side, and the control effect on the asymmetric flow is opposite.